(untitled) (TAJ: Journal of Teachers Association, 2009)
Myocardial Infarction (MI) is the most common form of heart disease and the single most important cause of premature death in the developed and developing world. Unfortunately the incidence of the condition is increasing rapidly in many developing countries like Bangladesh. Effort should therefore be taken to minimize the risk factors of MI. Large scale randomized clinical trials have shown that lowering high cholesterol concentration mainly by drugs reduces the risk of cardiac events like MI. This study was designed to see the serum cholesterol levels in normal healthy subjects, to compare serum cholesterol levels in patients with MI and those of healthy subjects and to evaluate the association of serum cholesterol level in Bangladesh MI patients. The present study was carried out in the Department of Biochemistry, BSMMU in collaboration with Department of Cardiology, BSMMU and NICVD, Dhaka during the period of July 2001 to December 2002. A total of 50 subjects were selected, Group A (30 subjects of Control) and Group B (20 subjects of MI). The mean level of serum cholesterol in control subjects were 145.07 ± 31.39 mg/dl and in test subjects were 226.91 ± 44.38 mg/dl. This study showed that serum cholesterol level was significantly higher in patients with MI. From the present study, it is difficult to draw any definite conclusion but suggested that high serum cholesterol concentration plays a crucial role in the pathogenesis of MI. doi: 10.3329/taj.v17i1.3483 TAJ 2004; 17(1) : 13-15